2002
DOI: 10.1039/b207238f
|View full text |Cite
|
Sign up to set email alerts
|

Cationic β-cyclodextrin bilayer vesicles

Abstract: Cationic amphiphilic beta-cyclodextrins, substituted with hydrophobic n-alkylthio chains at the primary hydroxyl side and hydrophilic omega-amino-oligo(ethylene glycol) units at the secondary side, form bilayer vesicles with a diameter of 30-35 nm (when alkyl = hexadecyl) or nanoparticles with a diameter of ca. 120 nm (when alkyl = hexyl) in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 26 publications
(8 reference statements)
2
83
0
1
Order By: Relevance
“…25 Briefly, β-CD was substituted on the primary side with lipophilic chains (C 12 ) by thioalkylation. 18,26 Introduction of amphiphilic moieties improves the transfection efficiency of cationic CDs. 18,22 Functionalization at the 2-position was by means of a copper-catalyzed "click" reaction, which represents an efficient and versatile strategy for modifying the secondary side with diverse groups, including cationic groups and polyethyleneglycol (PEG) chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…25 Briefly, β-CD was substituted on the primary side with lipophilic chains (C 12 ) by thioalkylation. 18,26 Introduction of amphiphilic moieties improves the transfection efficiency of cationic CDs. 18,22 Functionalization at the 2-position was by means of a copper-catalyzed "click" reaction, which represents an efficient and versatile strategy for modifying the secondary side with diverse groups, including cationic groups and polyethyleneglycol (PEG) chains.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The same authors reported the first examples of polycationic amphiphilic CDs by converting the terminal hydroxyls to amino groups through iodination (!30), azide substitution (!31), and reduction (!32). [65] These compounds were shown to entrap pDNA by forming nanoparticles that behaved similarly to Lipofectamine -derived lipoplexes in terms of transfection efficiency and toxicity against COS-7 and Hep G2 cells. [66] The authors correlated the gene-delivery capability of the vectors with the length of the hydrocarbon chain.…”
Section: Polycationic Cyclodextrins-pdna Complexes (Cdplexes)mentioning
confidence: 99%
“…This is not typical when compared to the other CD-based gene delivery vectors studied by our group (Cryan et al, 2004b; and is likely to be influencing the hydrophilic-hydrophobic balance within this CD. Changing the hydrophilic-hydrophobic balance can result in differences in the type of self-assembled complexes formed with amphiphilic CDs (Donohue et al, 2002), which may in turn affect uptake and transfection, as has been the case for lipoplexes (Ma et al, 2007).…”
Section: Discussionmentioning
confidence: 99%